1980
DOI: 10.1161/01.cir.61.5.955
|View full text |Cite
|
Sign up to set email alerts
|

Exercise capacity in patients with severe left ventricular dysfunction.

Abstract: SUMMARY Normal or near-normal exercise capacity has been thought to reflect normal left ventricular function. Many compensatory mechanisms could preserve exercise capacity in patients with severe left ventricular dysfunction. We evaluated exercise capacity using a treadmill exercise test in 26 patients with severe left ventricular dysfunction defined by a left ventricular ejection fraction of 30% or less by isotope ventriculography. One half of the patients had normal exercise capacity and a normal cardiothora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
54
0
6

Year Published

1983
1983
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(64 citation statements)
references
References 33 publications
(6 reference statements)
4
54
0
6
Order By: Relevance
“…1) Previous studies have demonstrated that left ventricular (LV) systolic function does not predict exercise capacity. 2,3) In contrast, recent reports showed that LV diastolic dysfunction was intimately related to functional status. 4,5) Although LV diastolic dysfunction is known to reduce exercise capacity, it is often difficult to predict precise exercise capacity by evaluating diastolic filling because hemodynamic parameters measured at rest are influenced by age, heart rate, loading condition, and the properties of the LV and left atria (LA).…”
mentioning
confidence: 94%
“…1) Previous studies have demonstrated that left ventricular (LV) systolic function does not predict exercise capacity. 2,3) In contrast, recent reports showed that LV diastolic dysfunction was intimately related to functional status. 4,5) Although LV diastolic dysfunction is known to reduce exercise capacity, it is often difficult to predict precise exercise capacity by evaluating diastolic filling because hemodynamic parameters measured at rest are influenced by age, heart rate, loading condition, and the properties of the LV and left atria (LA).…”
mentioning
confidence: 94%
“…Foram encontradas correlações fracas entre FEVE e VO 2pico (r=0,13; p<0,01) e também entre FEVE e VE/VCO 2 (r=-0,16; p<0,01) 26 . Apesar da disfunção ventricular esquerda poder alterar a capacidade de esforço, tem sido proposto que mecanismos compensatórios podem preservar a tolerância ao exercício, dentre eles: aumento do volume diastólico final, competência cronotrópica, aumento da extração de oxigênio, alteração da complacência ventricular esquerda ou, ainda, aumento do fluxo linfático pulmonar 27 . Assim, embora a intolerância ao exercício seja o maior sintoma destes pacientes, não parece existir relação direta entre a função sistólica e a capacidade de realização do exercício.…”
Section: Discussionunclassified
“…However, the LVEF cut-off chosen to define heart failure differs between studies: values of 35% [2], 40% [3] and 45% [4] have all been used; thus, patients included in many studies are not comparable. Furthermore, L YEF correlates poorly with exercise capacity [5]. Results from clinical trials are often difficult to apply to data collected by epidemiologists because their definitions and inclusion criteria often differ from those used by epidemiologists.…”
Section: Why Define Heart Failure?mentioning
confidence: 99%